SAMPLING OF AN OPTIMAL INITIAL CONDITION FOR THE MATHEMATICAL MODELS DESCRIBING PHYSICAL PROCESSES APPLYING INVERSE PROBLEMS - Sinisa, A.V.; Rysbayuli, B.R. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
This paper represents an overview of the suggested algorithm for sampling an optimal initial condition for the mathematical model describing real world physical processes. Proposed hypothesis suggests an implementation of the broad range of the theory of applied mathematics, videlicet the theory of inverse problems. As well as the theoretical basis, this paper gives a brief description of the analyses for the results obtained through the numerical experiment and purposely gives a direction for the further investigation for research on this topic.
Keywords: direct problem; inverse problem; initial conditions; heat transfer; multi - layered area; conjugate problem; iterative formula; balance method